Corporate Social Responsibility and Food Security (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the issues of corporate social responsibility (CSR) and food security. The role of CSR and food security is examined in the context of sustainable growth and development of the society. The paper also highlights the ethical dimensions of capitalist behaviour of the firms and its role in promoting food security. Some of the key research areas in the context of CSR and food security is also examined. The paper finally brings out some of the future research areas in the field.